Ultrasound-assisted enzymatic extraction of jujube (Ziziphus jujuba Mill.) polysaccharides: Extraction efficiency, antioxidant activity, and structure features - Yiting Guo; Shenao Nan; Chengcheng Qiu; Chenyu Song; Bengang Wu; Yanhua Tang; Lifang Cheng; Haile Ma (Ultrasonics Sonochemistry)
This study investigated the effect of ultrasound-assisted enzymatic extraction (UAEE) on the extraction efficiency, antioxidant activity, and structural properties of jujube polysaccharide (JPS), with hot water extraction (HWE), ultrasound-assisted extraction (UAE), and enzymatic-assisted extraction (EAE) serving as controls. Optimal extraction conditions were determined through a multi-index weighted scoring method that comprehensively accounted for yield, duration, and antioxidant activity. Results demonstrated that the JPS yield obtained by UAEE at 22/33 kHz was 10.5 % to 16.3 % higher than those achieved by the other methods, significantly enhancing antioxidant activity. Monosaccharide composition analysis revealed that UAEE increased the content of key mono-sugars in JPS. Additionally, assessments of molecular weight distribution, zeta potential, and rheological properties showed that UAEE reduced the molecular weight and apparent viscosity of JPS, resulting in a looser structural configuration. These structural modifications were observed in scanning electron microscope (SEM) images, which revealed a filamentous branched morphology in JPS obtained through UAEE. Further observations using the atomic force microscope (AFM) indicated that the polysaccharide chains extracted by UAEE were shorter in length, lower in height, and free from aggregation.